PENGARUH PENGEMBANGAN DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI DINAS KOPERASI DAN USAHA MIKRO KOTA SURABAYA PADA ERA PANDEMI COVID-19 - Zatik Mazidah; Mochamad Mochklas; Rina Maretasari (PROCEEDING UMSURABAYA, 2022)
Human resource development and quality are significant to improving company performance. This research aims to determine the effect of the product and quality of human resources on the performance of the Cooperative and Micro Business Office employees in Surabaya during the Covid-19 Pandemic Era. This research uses quantitative methods by testing hypotheses based on data obtained from distributing questionnaires to respondents. The data are collected using a questionnaire with a sample of 38 employees. The results of the research show that the independent variable (X1) is Human Resource Development and the independent variable (X2) is the Quality of Human Resources which simultaneously have a positive and significant effect on the dependent variable (Y) Employee Performance with the F test results obtained that f count 57.271 with a value significance 0.000<0.05. While partially the independent variable (X1), Human Resource Development, has a significant and positive impact on the dependent variable Employee Performance (Y) with a significance value of 0.000 <0.05, and the independent variable (X2) Human Resource Quality has a positive and significant effect on the dependent variable (Y ) Employee performance with a significance value of 0.001 <0.05.Keywords                   : Development; Quality of Human Resources; Employee Performance.